Crime News in Modern Britain - Rowbotham, Judith. author. aut Link
XI, 266 p.
Keywords: Drawing together examples from broadsheet and tabloid newspapers this account of English crime reportage takes readers from the late eighteenth century to the present day. In the post-Leveson world, it is a timely and engaging contextualisation of the history of printed crime news and investigative journalism.